Sibol Las Pinas Livelihood and Cultural Center - Riguera, Riva D.; Boot, Luis Ma. T. (Quezon City College of Architecture, University of the Philippines Diliman, 2017)
Urbanization is seen as a sign of progress, but it also comes with problems. There are many attempts in promoting the benefits and avoiding the ill effects of urbanization, but a big hurdle is the disconnect between the problems and the proposed solutions, between the government and the people, and between plans and reality. This thesis attempts to bridge the gap and create connections - points of interaction - towards continuous awareness, acknowledgement , and action through a reliable means of communication - sustainable local tourism in Las Piñas city through a livelihood and cultural hub. On the contrary, progress is not limited to urbanization alone. Hence, this thesis can be a stepping stone towards urban-rural inter-connection by starting with strengthening connections within the urban center.
Thesis (Bachelor of Science in Architecture)--University of the Philippines Diliman
Keywords: Cultural centers -- Las Pinas City -- Philippines